2018
DOI: 10.3233/jad-170552
|View full text |Cite
|
Sign up to set email alerts
|

Serum Non-Ceruloplasmin Non-Albumin Copper Elevation in Mild Cognitive Impairment and Dementia due to Alzheimer’s Disease: A Case Control Study

Abstract: Several studies showed high serum copper levels in Alzheimer's disease (AD). The present study applied a newly developed method to detect serum copper free from proteins (free-Cu). Forty-four patients affected by dementia due to AD, thirty-six patients affected by mild cognitive impairment (MCI) due to AD, and twenty-eight healthy controls underwent clinical, cognitive, and MRI assessment. The new method showed higher free-Cu concentrations in MCI and dementia due to AD compared to controls (p < 0.0001). No co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Several studies have indicated that the CP in the AD patients may be used as the new hallmarks in the serum [41]. Another ferric oxidase protein, HEPH, presents homology with CP, both of which participates in iron metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that the CP in the AD patients may be used as the new hallmarks in the serum [41]. Another ferric oxidase protein, HEPH, presents homology with CP, both of which participates in iron metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This is linked to an increased concentration of non-bound ceruloplasmin (non-Cp) copper in plasma along with a decrease in copper bound to ceruloplasmin (Cp), which is less prone to oxidative reaction [17]. In support of this notion, several studies have reported that non-Cp copper is higher in individuals with mild cognitive impairment (MCI) and Alzheimer’s disease when compared with healthy controls [54,55,56]. Furthermore, Squitti et al [57] demonstrated that non-Cp copper was the only significant predictor of clinical conversion from MCI toward Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…Total copper and the ratio of copper to non-heme iron distinguished progressive MCI subjects from cognitively stable MCI subjects in a five-year follow-up study [37]. Other cross-sectional studies also demonstrated that noncp-Cu is higher in MCI than in healthy controls [219,231,232]. Large population studies suggest that copper imbalances occur at early stages of cognitive loss and AD development, and copper in the soil has been associated with increased mortality relating to AD (Table 1) [233].…”
Section: Clinical Evidence: Copper Dyshomeostasis In Admentioning
confidence: 92%